Edukasi dan Skrining Kesehatan untuk Pencegahan Hipertensi di RT 10 Wonocatur, Banguntapan, Bantul, Yogyakarta - Solikhah Solikhah; Rizki Fadilah; Gadis Tara Tantri Wijaya; Aqsal Farisi; Annysa Marsamuna Nayla Dhiaulhaqi; Lutfia Sahanaya (JURNAL INOVASI HASIL PENGABDIAN (JIHAN), 2026)
Hypertension is one of the non-communicable diseases with an increasing prevalence and is often not realized by those affected. Based on the results of a community diagnosis in RT 10 Dukuh Wonocatur, hypertension was identified as one of the top three health problems, accompanied by low public awareness of routine blood pressure monitoring. This community service activity aimed to increase community knowledge and awareness in preventing hypertension through health education and health screening. The methods included blood pressure measurement and random blood glucose testing; health education on hypertension and the DASH diet; as well as evaluation using pre-test and post-test instruments. The activity was conducted in January 2026 and involved 20 residents of RT 10 Dukuh Wonocatur. The results showed an improvement in community knowledge, as indicated by higher post-test scores compared to pre-test scores. In addition, participants demonstrated a better understanding of risk factors, impacts, and the importance of hypertension control through regular blood pressure monitoring and the adoption of a healthy lifestyle. This activity is expected to serve as a sustainable promotive and preventive effort to reduce the risk of hypertension in the community